Nanotechnology in Periodontal Regeneration: A Review - Gargi Nimbulkar1 , Priyanka Multani2 , Khushbu Balsara2 , Kumar Gaurav Chhabra3 , Shravani Deolia4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Periodontitis involves destruction of the periodontal ligament and supporting structures. It ranges from asimple inflammation of gums to major damage resulting in loss of bone. Multiple conditions like trauma,periodontal disease, reconstructive surgery, ageing, osteoporosis and neoplastic pathology, have a commoncharacteristic feature being loss of bone and tissue. The regenerative procedures that are currently practicedaim to regenerate the lost tissue via means of grafting, placement of membranes and many more, but havebeen accompanied with a set of limitations and major disadvantage being graft rejection. Periodontalregeneration still endures to be a partially unsolved algorithm. In dentistry, a new arena of developmentis being exploited to set a new approach for regeneration that is Nanotechnology. This branch involvestissue engineering which aims to regenerate the lost tissues via manufacturing scaffolds which transportsignaling cells and molecules. These scaffolds possess magnificent physical as well as chemical propertiesand biomimetic features that act as a substitute of the highest standard offering innumerable benefits forpromoting cell growth and tissue regeneration via tissue engineering.Nanomaterials because of their refinedphysiochemical characteristics and biomimetic attributes serve as a scope worthy substitute that offersseveral advancements for stimulation of cell growth and tissue regeneration. This review provides an insightto basic information about nanotechnology, the various nano particles having application in periodontalregeneration, the advanced regenerative procedures fabricated on the principles of nanotechnology, theirapplications, the clinical studies highlighting the achievements so far, supremacy over the conventionalmethod and limitations.